Observer-Based Adaptive Finite-Time Containment Control for Nonlinear Multiagent Systems Subject to FDI Attacks - Kang, Haobo; Ma, Hongjun; Niu, Ben (IEEE transactions on automation science and engineering, 2025)
This paper investigates the adaptive finite-time containment control problem for a class of nonlinear multiagent systems (MASs) under false data injection (FDI) attacks. On account of the fact that instability is inevitable when the false datas are injected into the researched system, the backstepping technique based on the modified coordinate transformation is applied to eliminate the impact of the FDI attacks. Furthermore, the "dynamic surface control"(DSC) approach is utilized to overcome the issue of "explosion of complexity" caused by repeatedly taking derivatives for the virtual control laws. Then, by designing an observer to refactor the immeasurable states of the MASs, a finite-time adaptive output-feedback tracking containment controller is constructed. It is shown that all the signals in the closed-loop systems are semi-globally practical finite-time stability(SGPFS), and the outputs of all the followers converge to the convex hull spanned by the multiple leaders's outputs. Besides, the observer errors and the containment errors can converge to a small neighborhood of the origin in finite time. Finally, the simulation results are presented to demonstrate the effectiveness of the proposed containment control protocol. Note to Practitioners-The containment control problem is a hot topic in the field of control, which plays an important role in practical engineering. Especially for this problem of nonlinear MASs, the mathematical models are difficult to be obtained accurately. This paper investigates the adaptive finite-time containment control problem for the nonlinear MASs, whose model can be extended to more complex engineering applications, such as UAV formations and intelligent traffic management. It is worth noting that network security and unmeasured state problems often exist in practical applications. Therefore, by designing an observer to refactor the immeasurable states of the MASs, it is ensured that all the signals in the closed-loop systems are SGPFS. To sum up, the paper proposes an adaptive finite-time containment control strategy, which contributes to the development of containment control for MASs in practical applications.